A dual role for hepatocyte-intrinsic canonical NF-[kappa]B signaling in virus control - Namineni, Sukumar; O'Connor, Tracy; Faure-Dupuy, Suzanne; Johansen, Pal; Riedl, Tobias; Liu, Kaijing; Xu, Haifeng; Singh, Indrabahadur; Shinde, Prashant; Li, Fanghui; Pandyra, Aleksandra; Sharma, Piyush; et al. (Journal of hepatology, 2020)
Background & Aims: Hepatic innate immune control of viral infections has largely been attributed to Kupffer cells, the liver-resident macrophages. However, hepatocytes, the parenchymal cells of the liver, also possess potent immunological functions in addition to their known metabolic functions. Owing to their abundance in the liver and known immunological functions, we aimed to investigate the direct antiviral mechanisms employed by hepatocytes. Methods: Using lymphocytic choriomeningitis virus (LCMV) as a model of liver infection, we first assessed the role of myeloid cells by depletion prior to infection. We investigated the role of hepatocyte-intrinsic innate immune signaling by infecting mice lacking canonical NF-kappa B signaling (Ikk beta(Delta Hep)) specifically in hepatocytes. In addition, mice lacking hepatocyte-specific interferon-alpha/beta signaling-(Ifnar(Delta Hep)), or interferon-alpha/beta signaling in myeloid cells-(Ifnar(Delta Myel)) were infected. Results: Here, we demonstrate that LCMV activates NF-kappa B signaling in hepatocytes. LCMV-triggered NF-kappa B activation in hepatocytes did not depend on Kupffer cells or TNFR1 signaling but rather on Toll-like receptor signaling. LCMV-infected Ikk beta(Delta Hep) livers displayed strongly elevated viral titers due to LCMV accumulation within hepatocytes, reduced interferon-stimulated gene (ISG) expression, delayed intrahepatic immune cell influx and delayed intrahepatic LCMV-specific CD8(+) T cell responses. Notably, viral clearance and ISG expression were also reduced in LCMV-infected primary hepatocytes lacking IKK beta, demonstrating a hepatocyte-intrinsic effect. Similar to livers of Ikk beta(Delta Hep) mice, enhanced hepatocytic LCMV accumulation was observed in livers of Ifnar(Delta Hep) mice, whereas IfnarDMyel mice were able to control LCMV infection. Hepatocytic NF-kappa B signaling was also required for efficient ISG induction in HDV-infected dHepaRG cells and interferon-alpha/beta-mediated inhibition of HBV replication in vitro. Conclusions: Together, these data show that hepatocyte-intrinsic NF-kappa B is a vital amplifier of interferon-alpha/beta signaling, which is pivotal for strong early ISG responses, immune cell infiltration and hepatic viral clearance. Lay summary: Innate immune cells have been ascribed a primary role in controlling viral clearance upon hepatic infections. We identified a novel dual role for NF-kappa B signaling in infected hepatocytes which was crucial for maximizing interferon responses and initiating adaptive immunity, thereby efficiently controlling hepatic virus replication. (c) 2020 Published by Elsevier B.V. on behalf of European Association for the Study of the Liver. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-ncnd/4.0/).